Design and validity of a questionnaire to assess sexuality in pregnant women - Rudge, Cibele Vieira Cunha [UNESP]; Calderon, Iracema de Mattos Paranhos [UNESP]; Dias, Adriano [UNESP]; Lopes, Gerson P.; Barbosa, Angélica P. [UNESP]; Maestá, Izildinha [UNESP]; Odland, Jon Øyvind; Rudge, Marilza Vieira Cunha [UNESP] (Springer Nature, 2009)
Background. A review of validated methods for assessing female sexual dysfunction and a review of male and female sexual dysfunction did not refer to any specific questionnaire for evaluating sexuality during pregnancy. A study was performed at the Obstetrics and Gynecology Department of Botucatu Medical School, São Paulo State University, Brazil to design and validate a pregnancy sexuality questionnaire, the Pregnancy Sexual Response Inventory (PSRI). Methods. Women with a singleton pregnancy between 10 and 35 weeks of gestation were randomly recruited. There were five phases in the development of the PSRI: (1) item selection; (2) item development; (3) determination of internal consistency, reliability and convergence; (4) content validity; and (5) determination of inter-interviewer reliability. Internal consistency and reliability were evaluated using Cronbach's alpha. Inter-interviewer reliability was assessed by evaluating the responses of 18 academics at various institutions, using Kappa Index and Student t test. Results. Good internal consistency and reliability were obtained (Cronbach's alpha coefficient = 0.79). Among the 18 academics, 13 totally agreed (K = 1.0), three partially agreed (K = 0.67) and two disagreed (K = 0.33) with the proposed questions. Comparisons of the mean PSRI domain scores made between the primary investigators and the other interviewers showed no significant differences in all domains (p > 0.05). Conclusion. PSRI is a new validated instrument for evaluating sexuality and sexual activity and related health concerns during pregnancy. © 2009 Rudge et al; licensee BioMed Central Ltd.
Keywords: Brazil; content validity; cross-sectional study; female; gestational age; human; internal consistency; major clinical study; outcome assessment; pregnancy; questionnaire; reliability; sexual behavior; sexuality; validity